Corporate Social Performance and Corporate Financial Performance: A Link for the Indian Firms (Issues in Social and Environmental Accounting (ISEA), 2013)
The present study addresses the issue of the relationship between Corporate Social performance and corporate Financial Performance in Indian context under good management theory. The study used S&P ESG India Index as a proxy of CSP/ CSR (Corporate social performance or Corporate Social Responsibility) of Indian firms for the first time over the 2005–2011 periods. We designed econometric models and controlled industry specific attributes and performed Weighted Least Square method for the analysis. Overall results show neutral though modest negative relationship between the CSP and CFP which eventually informs that if there would be any relationship, it would be negative.